Spatial segregation, inequality, and opportunity bias in the slums of Bengaluru. (April 2018) - Roy, Debraj; Lees, Michael Harold; Pfeffer, Karin; Sloot, Peter M.A.
Abstract: The existence of slums or informal settlements is common to most cities of developing countries. In India, slums contain a wealth of diversity that is masked by a high level of poverty and rather insufficient access to resources. Recent studies have identified that the conventional perception of slums as distinctive homogeneous settlements is incorrect, rather slums are diverse and complex systems that cannot be addressed through one-size fits all approaches. In this paper we investigate Tilly's theory on group segregation and how it reproduces or reinforces inequality within the slums of Bengaluru. We apply statistical techniques (correspondence analysis and regression) to novel field data from 37 slums in Bengaluru. First, we find high levels of spatial and group segregation by religion across the slums of Bengaluru. Second, we find that segregation leads to opportunity bias among slum dwellers, which inhibits equitable access to jobs in the labour market. Finally, the results show that insufficient access to resources constrain the income generation and leads to emerging coping strategies. The results indicate that group identity is key to addressing disparity and how solving inequality can drastically impact group identity. Our results show that targeting horizontal inequality (as compared to vertical inequality ) may increase the rate of successful interventions for each of the segregated groups of slum dwellers. Highlights: High levels of social and spatial segregation by religion and occupation in the slums of Bangalore based on novel on-field survey data of 37 slums Results show that solving horizontal inequality (as compared to vertical inequality) can increase the rate of successful interventions. High degree of inequality and opportunity bias inhibits equitable access to jobs in the labour market. Insufficient access to resources constrains the income generation and leads to emerging coping strategies.